2021
DOI: 10.3390/app11093791
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis and Shape Optimization of Airfoils Using Class Shape Transformation and Genetic Algorithm—Part I

Abstract: This paper presents the parameterization and optimization of two well-known airfoils. The aerodynamic shape optimization investigation includes the subsonic (NREL S-821) and transonic airfoils (RAE-2822). The class shape transformation is employed for parametrization while the genetic algorithm is used for optimization purposes. The absolute scheme of the optimization process is carried out for the minimization of the drag coefficient and maximization of lift to drag ratio. In-house MATLAB code is incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Firstly, for thermal networks containing internal combustion engines, waste heat boilers, gas boilers, and thermal loads, during the sampling period 0 t The initial measurement values of the output and heat load of internal combustion engines, waste heat boilers, and gas boilers are used as the initial state, and the power state vector is established as follows: (10) In the equation: T  Is the scheduling duration;  …”
Section: Optimization Of Thermal System Operationmentioning
confidence: 99%
“…Firstly, for thermal networks containing internal combustion engines, waste heat boilers, gas boilers, and thermal loads, during the sampling period 0 t The initial measurement values of the output and heat load of internal combustion engines, waste heat boilers, and gas boilers are used as the initial state, and the power state vector is established as follows: (10) In the equation: T  Is the scheduling duration;  …”
Section: Optimization Of Thermal System Operationmentioning
confidence: 99%
“…For the reader's convenience, it is noted that a design variable vector ŵ is Pareto-dominated by another design variable vector w if 𝑓 𝑘 ( ŵ) ≤ 𝑓 𝑘 ( w) for all To obtain the Pareto-front, especially when objectives cannot be weighted or when a non-convex black-box function is considered, evolutionary or genetic algorithms are a natural choice [70,76]. In fact, they have been commonly implemented in many previous aerodynamic optimization studies due to their gradient-free nature and wide region of the search domain [31,[77][78][79]. On the other hand, when the cost functions are expensive to compute (e.g.…”
Section: Optimizationmentioning
confidence: 99%
“…One typical way of determining the basis modes is through proper orthogonal decomposition (POD) of a set of airfoil data, and dimensionality can be reduced by using only the dominant modes [27,28]. Other methods include the Hicks-Henne's approach [29], which uses a linear combination of sine functions to deform the airfoil surface, and class/shape function transformation (CST) method proposed by Kulfan [30,31], which represents an airfoil shape as the product of a class function and a shape function formed by a linear combination of Bernstein polynomials. Similar to all the other methods on the spectrum, in order to resemble high-fidelity features, more basis modes have to be included, which again falls into the so-called the curse of dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…Meerimatha et al [21] investigated the effect of partial shading on the power output by reconfiguring PV arrays using a Genetic algorithm. Rajan et al [22] studied PV array reconfiguration using the concept of standard deviation and GA. Akram et al [23] concluded that the GA and Class Shape Transformation techniques couldbe very efficient for optimizingairfoil shapes. Using these techniques, a reduction in drag coefficients of 10% and 12% was achieved, while the lift-to-drag ratios improved by 7.4% and 15.9% for two different airfoils.…”
Section: Introductionmentioning
confidence: 99%